Pianificazione antincendio nell'interfaccia urbano-rurale in ambiente GIS open source: il caso studio della Regione Puglia: Le zone di interfaccia urbano-rurale, dove le strutture antropiche confinano con le aree naturali o seminaturali, sono particolarmente vulnerabili agli incendi, rappresentando una minaccia per persone, edifici e infrastrutture.Queste aree richiedono interventi pianificatori specifici. Nel 2007, dopo una stagione estiva caratterizzata da numerosi incendi che hanno colpito in particolare le aree di interfaccia, il Dipartimento della Protezione Civile Nazionale ha elaborato le linee guida per affrontare il rischio incendi in queste aree a scala comunale. Tali linee guida rappresentano il riferimento per la metodologia che viene presentata in questo articolo. (GEOmedia, 2025)
Urban-rural interface areas, where man-made structures border natural or semi-natural areas, are particularly vulnerable to fire, posing a threat to people, buildings and infrastructure.These areas require specific planning interventions. In 2007, after a summer season marked by numerous fires that particularly affected interface areas, the Department of National Civil Defense developed guidelines to address fire risk in these areas. These guidelines were the starting point for implementing the methodology that is presented in this paper. In this paper, a preliminary and expeditious methodology is proposed to improve the current protocol of the Italian Civil Defense regarding urban-rural interface fires. Specifically, it involves the creation of some information layers based on the integration of different open data available online. These layers thus created are intended to be considered within a vulnerability index and a hazard index, in order to combine both to assess the risk within interface zones. The municipality of San Giovanni Rotondo (FG) was chosen as a real case. All operations performed are based on QGIS software.